Biocatalytic Synthesis of Fluorescent Conjugated Indole Oligomers - Ryan M. Bouldin (Bioengineering, 2014)
Fluorescent conjugated materials exhibiting reasonable biocompatibility that are capable of interacting with biological molecules are of interest for bio-sensing and imaging applications. Traditional approaches do not allow for the synthesis of conjugated materials in the presence of biologically relevant substrates. Further conjugated polymers synthesized using conventional methods are doped and not fluorescent. Here we explore the possibility of synthesizing fluorescent oligomers of indole using enzymes as catalyst under mild conditions. The peroxidase catalyzed coupling reaction presented here creates a photoluminescent material that allows for direct utilization (without purification and separation of the dopant) in biosensing applications. The polymerization reaction proceeds smoothly in just deionized water and ethanol. Monitoring of the absorption and fluorescence spectra over one hour shows that the concentration of both absorbing and emitting species grows steadily over time. The presence of anionic buffers and templates is shown to effectively retard the development of light emitting species and instead leads to the formation of an electrically doped conjugated polymer. Structural characterization through FTIR and 1H-NMR analysis suggests that the oligomer is coupled through the 2 and 3 positions on the indole ring.